Modern Slavery Made in Italy—Causes and Consequences of Labour Exploitation in the Italian Agricultural Sector - Ruggero Scaturro (Journal of Illicit Economies and Development, 2021)
Through this paper, the author emphasises the importance of the role that migrant women and men play in the Italian agricultural sector, and the need to better protect them from forms of labour exploitation. Italian products are well known all over the world and represent the excellency of an entrepreneurial fabric made of thousands of family-run small and medium enterprises which from the Alps to Sicily produce unique fruits, vegetables, food, and wines. But a long history of illegal recruitment and labour exploitation, known in Italy as caporalato, tarnish the long supply chain which brings Italian agri-food products to dining tables and market shelves across the globe. In addition, to cope with the forms of exploitation occurring in the Italian countryside, this the paper points out the need to harmonise norms and regulation on labour, migration, and human rights. In doing so, it also argues that both the mens legislatoris and law enforcement authorities modus operandi should progressively move from an approach which is based on a relentless pursuit of the organized crime component for criminalising the acts of labour exploitation and illegal recruitment as defined in the criminal code, to a more comprehensive and holistic approach which puts the rights of migrant agricultural workers as the agenda’s top priority.